Adaptation and psychological problems and suggestions for solution of foreign students studying at medical faculty (Annals of Medical Research, 2021)
Aim: Students who change places due to social, economic, geographical, cultural, and war reasons are likely to experience difficulties while adapting to the new environment. The aim of this study is to identify adaptation and psychological problems experienced by foreign students and to present suggestions to faculty education commissions to improve the health and education conditions.Materials and Methods: The study was conducted between January and March 2020. The universe of the study consisted of all foreign students in the 2019-2020 academic year studying at the medical school. No sampling method was used in the study by aiming to reach the entire population. Foreign students studying at the Faculty of Medicine filled out a questionnaire including the educational problems experienced by the students and Beck’s Depression Inventory (BDI).Results: The most common problems of foreign students were as; language problems in 50 (49.0%) students, being away from family in 31 (30.4%) students, and financial problems in 21 (20.6%) students. It was found that 39.2% (n = 40) of the students had minor depression, 29.4% (n = 30) had mild depression, 26.5% (n = 27) had moderate depression and 4.5% (n = 5) had severe depression scores according to BDI. 69.5% of the students stated that they faced negative behaviors because they were foreigners.Conclusion: Supportive interventions can prevent the development of depression by providing academic and psychological relief to foreign students.